مدى إتقان طلبة قسم تكنولوجيا التعليم بجامعة إب اليمنية لمهارات مستحدثات تكنولوجيا التعليم. - Al-Hidabi, Dawood Abdulmalek Yahya; Saleh, Issa Muhammad Ali (2019)

(untitled)
This study attempted to investigate to what extent students of educational technology department at Ibb University in Yemen are competent in using ICT skills in education. The descriptive research method was used and a sample of 20 students was selected from the secondyear students for the academic year 2018/2019. An observation schedule was developed and standardized for measuring students’ ICT skills. A program for acquiring the uses of ICT skills in education was developed and implemented with the study sample. The result showed that students’ competency of ICT skills was average. The study also offers a set of recommendations to improve the effective use of ICT skills by students at the department of educational technology, Ibb University in Yemen.